Dampak Pengasuhan Lansia Terhadap Perilaku Digital Generasi Alpha: Kajian Literatur Sistematis - Angela Olivia Lubis; Zarina Akbar; Mira Ariyani (Universitas Medan Area, 2026)
This study aims to synthesize scientific findings related to the role of older adults as primary caregivers and its impact on the digital behavior of Generation Alpha children and adolescents. Using the Systematic Literature Review (SLR) method, this study analyzed 15 relevant scientific articles published in the last ten years. The results of the analysis show that the elderly (grandparents) play a crucial role as mediators of their grandchildren's digital media use. However, the effectiveness of this mediating role is significantly hampered by the elderly's limited digital literacy and psychological pressures. This skills gap leads to inconsistent screen regulation, which significantly increases the risk of problematic digital behavior in grandchildren. Furthermore, it was identified that the long-term impact of elderly caregiving on grandchildren's digital addiction is mediated by their psychosocial vulnerability as they enter adulthood, namely social anxiety and loneliness. The conclusions of this study emphasize the need for structured interventions in the form of age-sensitive digital literacy education for the elderly, as well as policies that support collaborative intergenerational caregiving to shape healthy digital behavior in Generation Alpha.